2013
DOI: 10.1002/jbt.21472
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gene Polymorphism of Manganese Superoxide Dismutase and Prostate Cancer Risk

Abstract: Manganese superoxide dismutase (Mn-SOD) is the most effective antioxidant enzyme in mitochondria and protects cells from reactive oxygen species-induced oxidative damage. The aim of this study was to investigate the association between Mn-SOD Ala-9Val gene polymorphism and prostate cancer (PCa) risk in Turkish men with prostate cancer. 33 patients with PCa and 81 control individuals were included in the study. We observed an association between MnSOD Ala/Ala frequency and a higher PCa risk. In addition, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Overall, 88 studies with 33,098 cases and 37,831 controls were included in this meta-analysis. Of the 88 studies, 24 studies focused on breast cancer [ 9 11 , 16 , 38 , 60 , 61 , 68 , 69 , 71 , 72 , 77 , 88 , 93 , 96 , 97 , 100 , 105 , 109 , 114 , 119 , 122 , 127 ]; 17 on prostate cancer [ 37 , 66 , 74 , 79 , 82 , 85 , 86 , 89 , 95 , 106 , 111 , 113 , 120 , 125 , 128 ]; six for each of the following cancer types, such as lung cancer [ 7 , 17 , 18 , 65 , 92 , 118 ], bladder cancer [ 8 , 15 , 67 , 75 , 112 , 117 ], and pancreatic cancer [ 64 , 91 , 102 , 107 , 108 , 121 ]; five on colorectal cancer [ 13 , 63 , 73 , 94 , 101 ]; three for each of the following cancer types, such as ovarian cancer [ 70 , 81 , 87 ], hepatocellular carcinoma [ 98 , 99 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 88 studies with 33,098 cases and 37,831 controls were included in this meta-analysis. Of the 88 studies, 24 studies focused on breast cancer [ 9 11 , 16 , 38 , 60 , 61 , 68 , 69 , 71 , 72 , 77 , 88 , 93 , 96 , 97 , 100 , 105 , 109 , 114 , 119 , 122 , 127 ]; 17 on prostate cancer [ 37 , 66 , 74 , 79 , 82 , 85 , 86 , 89 , 95 , 106 , 111 , 113 , 120 , 125 , 128 ]; six for each of the following cancer types, such as lung cancer [ 7 , 17 , 18 , 65 , 92 , 118 ], bladder cancer [ 8 , 15 , 67 , 75 , 112 , 117 ], and pancreatic cancer [ 64 , 91 , 102 , 107 , 108 , 121 ]; five on colorectal cancer [ 13 , 63 , 73 , 94 , 101 ]; three for each of the following cancer types, such as ovarian cancer [ 70 , 81 , 87 ], hepatocellular carcinoma [ 98 , 99 , ...…”
Section: Resultsmentioning
confidence: 99%
“…SOD2, a key mitochondria manganese‐dependent SOD, which converts superoxide to hydrogen peroxide that is broken down further into water and oxygen by other enzymatic and non‐enzymatic antioxidant . SOD is of great importance in protecting cells from the damages induced by ROS . Souza et al showed that the combination of IL‐1β, TNF‐α and the pro‐inflammatory cytokine increased the level of SOD2 expression in both mRNA and protein levels .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 15 case-control studies including 6,958 cases and 7,961 controls met the inclusion criteria and were involved in the current meta-analysis (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The details of each study are listed in Tables I and II.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Recently, it has been demonstrated that a T-to-C substitution in the SOD2 gene could result in a valine (Val) to alanine (Ala) amino acid change, thus causing higher MnSOD enzymatic activity. Moreover, a growing number of studies have discovered a connection between the MnSOD Val16Ala polymorphism (rs4880) and the risk of PCa (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Therefore, this single-nucleotide polymorphism might play an important role in prostate carcinogenesis.…”
mentioning
confidence: 99%